SISTEM BIOGAS SEBAGAI ENERGI TERBARUKAN SKALA RUMAH TANGGA DENGAN MEMANFAATKAN LIMBAH KOTORAN BURUNG PUYUH - Elfiano, Eddy; Fadhilah, Muhammad Cendekia; Masdar, Mohd Shahbudin (Journal of Renewable Energy and Mechanics, 2019)
Bioenergy development is very important as a source of energy supply in the future. One of the bioenergy that can be developed to be used in the household is biogas energy. Biogas production process through anaerobic degradation of organic materials such as livestock is one of the technological solutions to produce alternative energy. The objective of this study is to obtain a simple household biogas system design with quail manure waste material. The method used in this study is an experimental method by measuring differences in manometer height, biogas pressure, gas volume development, gas volume, biogas production, and flame test. This study used quail and water manure with a ratio of 1: 1 at a digester capacity of 0.121 m3. Data collection was carried out for 50 days. In this research, the household scale biogas system constructed of a fiber glass drum with 44 cm diameter and 80 cm height. The results show that pressure generated for 50 days is 104,895 N / m2, with the development of the volume of gas per day an average of 0.047 m3, the volume of biogas produced for 50 days is 1.82 m3, and produces a flame on the stove for 1 hour 36 minutes.